Damping behavior of 3D woven metallic lattice materials. (September 2015) - Ryan, Stephen M.; Szyniszewski, Stefan; Ha, Seunghyun; Xiao, Rui; Nguyen, Thao D.; Sharp, Keith W.; Weihs, Timothy P.; Guest, James K.; Hemker, Kevin J.
Abstract : Cu and NiCr metallic lattice materials of two different micro-architectures were manufactured with a 3D weaving process. Dynamic mechanical analysis experiments demonstrated that the damping properties of these materials are much greater than their bulk counterparts and were found to have damping loss coefficients comparable to polymers, but with much higher maximum use temperatures. The magnitude of the damping phenomenon is characterized experimentally, and the importance of Coulomb (frictional) damping and inertial damping are investigated using a finite element model.